Role of general practitioners in care of long term mentally ill patients. - Kendrick, T; Sibbald, B; Burns, T; Freeling, P (1991)
OBJECTIVE: To assess general practitioners' involvement with long term mentally ill patients and attitudes towards their care. DESIGN: Postal questionnaire survey. SETTING: General practices in South West Thames region. SUBJECTS: 507 general practitioners, 369 (73%) of whom returned the questionnaire. MAIN OUTCOME MEASURES: The number of adult long term mentally ill patients whom general practitioners estimate they have on their lists and general practitioners' willingness to take responsibility for them. RESULTS: 110 respondents had noticed an effect of the discharge of adult long term mentally ill patients on their practices. Most (225) respondents estimated that they had 10 or fewer such patients each on their lists. Having higher numbers was significantly associated with practising in Greater London or within three miles of a large mental hospital and having contact with a psychiatrist visiting the practice. 333 general practitioners would agree to share the care of long term mentally ill patients with the psychiatrist by taking responsibility for the patients' physical problems. Only 59 would agree to act as a key worker, 308 preferring the community psychiatric nurse to do it. Only nine had specific practice policies for looking after long term mentally ill patients and 287 agreed that such patients often come to their general practitioner's attention only when there is a crisis. CONCLUSIONS: The uneven distribution of long term mentally ill patients suggests that community pyschiatric resources might be better targeted at those practices with higher numbers of such patients. Most general practitioners seem to be receptive to a shared care plan when the consultant takes responsibility for monitoring psychiatric health with the community nurse as key worker. The lack of practice policies for reviewing the care of long term mentally ill patients must limit general practitioners' ability to prevent crises developing in their care.